How to recover lithium from discarded lithium-ion batteries

JP7638266B2Active Publication Date: 2025-03-03BASF SE
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2022504575
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-01-14
Filing Date
2020-07-24
Publication Date
2025-03-03
Estimated Expiration
2040-07-24

AI Technical Summary

Benefits of technology

【0016】 したがって、本発明は主として、Li塩としてリチウムを、廃棄リチウムイオン電池又はそのパーツを含む材料から回収する方法であって、 (a)遷移金属化合物及び/又は遷移金属を含有する微粒子状材料を準備するステップであり、遷移金属が、Mn、Ni及びCoからなる群から選択され、さらに、存在する場合、該Ni及び/又はCoの少なくとも一部分が、+2よりも低い酸化状態にあり、存在する場合、該Mnの少なくとも一部分が酸化マンガン(II)であり、微粒子状材料が、リチウム塩及びフッ化物塩をさらに含有し、微粒子状材料が、場合によりカルシウムを含有し、ただし、カルシウムとフッ素との元素比(element ratio calcium to fluorine)(すなわちモル比、mol Ca:mol F)が、1.7以下又はゼロである、ステップ、 (b)ステップ(a)において準備した材料を、極性溶媒及びアルカリ土類水酸化物によって処理するステップ、並びに (c)固体を液体から分離し、場合により続いて、固体残留物を極性溶媒、例えば水によって洗浄するステップ を含む、方法に関係する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007638266000007
    Figure 0007638266000007
  • Figure 0007638266000008
    Figure 0007638266000008
  • Figure 0007638266000009
    Figure 0007638266000009
Patent Text Reader

Abstract

A method for recovering lithium from discarded lithium-ion batteries or parts thereof is disclosed. The method includes the steps of: (a) preparing a particulate material containing a transition metal compound and / or a transition metal, the transition metal being selected from the group consisting of Mn, Ni, and Co, and further wherein at least a portion of the Ni and / or Co, if present, is in an oxidation state lower than +2, and at least a portion of the Mn, if present, is manganese(II) oxide, the particulate material further containing a lithium salt and a fluoride salt, and optionally containing calcium, with the proviso that the elemental ratio of calcium to fluorine is 1.7 or less or zero; (b) treating the material prepared in step (a) with a polar solvent and an alkaline earth hydroxide; and (c) separating the solid from the liquid, optionally followed by washing the solid residue with a polar solvent, such as water, provides good separation of lithium at high purity and recovery of valuable transition metals.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention is directed to a method for recovering lithium from spent lithium-ion batteries containing at least one of the transition metals nickel, manganese and cobalt, and in particular relates to separating lithium from undesirable impurities by extracting it as lithium hydroxide from particulate material obtained from lithium-ion batteries, particularly the cell materials thereof, typically after discharge, crushing and reduction at high temperatures. [Background technology]

[0002] The storage of electrical energy is a subject of growing interest. Efficient storage of electrical energy allows for the generation of electrical energy when and where it is needed. Secondary lithium batteries are of particular interest for energy storage because, due to the small atomic weight and large ionization energy of lithium, they provide high energy density and have become widely used as power sources for many portable electronic devices, such as mobile phones, laptop computers, mini cameras, etc., as well as for electric vehicles. In particular, the increasing demand for raw materials, such as lithium, cobalt, and nickel, will create challenges in the future.

[0003] The life span of lithium-ion batteries is not unlimited. Therefore, it is expected that an increasing number of used lithium-ion batteries will be generated. Since lithium-ion batteries contain important transition metals, such as but not limited to cobalt and nickel, as well as lithium, used lithium-ion batteries may form a valuable source of raw materials for the new manufacture of lithium-ion batteries. For this reason, an increasing number of research activities are being carried out with the goal of recycling transition metals and lithium from second-hand lithium-ion batteries or from batteries or parts thereof that do not meet specifications and requirements (such off-specification materials and production waste may also be a source of raw materials).

[0004] Two main processes are targeted for raw material recovery: one is based on the smelting of the corresponding battery scrap, whereby a metal alloy containing Ni and Co is obtained, while the lithium is lost in the slag, from which it is very difficult to recover. This metal alloy can be processed by hydrometallurgy to extract metals, for example transition metals.

[0005] The other main process is the direct hydrometallurgical processing of battery scrap materials. The principle is disclosed in WO 2017 / 091562 and J. Power Sources, 2014, 262, 255 ff. Such hydrometallurgical processes provide transition metals as aqueous solutions, for example as sulfate solutions, or in precipitated form, for example as hydroxides, separately or already with the stoichiometries desired for making new cathode active materials. In the latter case, the composition of the metal salt solution may be adjusted to the desired stoichiometry by adding single metal components.

[0006] WO 2017 / 091562 describes the co-precipitation of transition metals. WO 2014 / 180743 describes a co-precipitation process using ammonia or amines.

[0007] Typically, the batteries are first disassembled into modules or even into cells. In the case of direct hydrometallurgical processes, the battery scrap is mechanically processed to separate larger parts from the casing and wiring. The electrode active material, i.e. graphite in the case of the anode and lithium transition metal oxide in the case of the cathode, together with some impurities, forms a fine powder, the so-called black mass or black powder, which constitutes the feed for the subsequent hydrometallurgical process steps. In some processes, the battery scrap is subjected to a heat treatment or pyrolysis step carried out at a temperature well below the melting point of the transition metals contained in the scrap, in this respect differing from the refining process, which operates at a temperature above the melting point of the transition metals contained in the scrap.

[0008] Such heat-treated black mass can result from the treatment of batteries in a waste incineration oven. Waste batteries, or battery modules or cells, are fed to the incineration oven, where the battery feed is partially combusted. The products of this treatment are cooled and mechanically treated using any type of crushing or grinding equipment suitable for separating the metal fraction from the powdery black mass. These black masses are low reactive materials under normal conditions and can therefore be easily transported.

[0009] Heat treatment at high temperatures above 400 °C of waste lithium-ion batteries or parts containing the electrode active materials of these types of batteries has been described by several authors. Such heat treatment completely evaporates the electrolyte solvent contained by the battery and decomposes the polymer components. The material resulting from such heat treatment may be subjected to different mechanical treatments and separation operations in order to separate the different metal fractions and powder materials, mainly comprising the electrode active materials from the anode, i.e. graphite, and the electrode active materials from the cathode, i.e. lithium-containing transition metal materials. These powders are often called "black mass" or "black powder", or "active mass". Depending on the reaction conditions, the latter materials are often at least partially reduced, thereby containing metallic Ni and Co phases, manganese oxide phases, and lithium salts such as LiOH, Li2CO3, LiF, LiAlO2, Li3PO4. The reduction occurs either by the introduction of reducing gases such as hydrogen or carbon monoxide during the heat treatment, or by the carbonaceous materials contained in the waste battery material, i.e. graphite and soot, at temperatures above 500° C. J. Li et al., J. Hazard. Mat. 2016, 302, 97 ff. discloses an oxygen-free roasting / wet magnetic separation process for the reclamation of cobalt, lithium carbonate and graphite from spent LiCoO2 / graphite batteries.

[0010] In JP2012-229481, waste batteries are treated in multiple steps in a way that binds the fluorine they contain in a conductive electrolyte salt, usually LiPF6, and a binder polymer, usually polyvinylidene fluoride (PVDF). This is achieved by first treating the waste batteries with an aqueous calcium hydroxide (slaked lime) solution to hydrolyze the conductive salt and precipitate the fluoride as calcium fluoride. Starting from conversion experiments with model substances such as LiCoO2, JP2012-229481 discloses a method for recovering metals from used lithium-ion batteries, including a pre-soaking step, followed by aqueous treatment with high-temperature oxidation, reduction roasting, filtration, and recovery of lithium carbonate from the filtrate and transition metals from the residue. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] International Publication No. 2017 / 091562 [Patent Document 2] International Publication No. 2014 / 180743 [Patent Document 3] JP 2012-229481 A [Non-patent literature]

[0012] [Non-Patent Document 1] J. Power Sources, 2014, 262, 255 ff. [Non-Patent Document 2] J. Li et al., J. Hazard. Mat. 2016, 302, 97 ff Summary of the Invention [Problem to be solved by the invention]

[0013] Known methods of recovering valuable materials typically face the problem that used batteries, i.e. the cells in which they are and contain the majority of these materials, contain high levels of impurities such as fluorine and / or phosphorus compounds, which must be removed in order to recover the desired materials (battery grade materials) in a purity that can be used for the production of new cells. It is therefore an object of the present invention to provide a method that allows easy recovery of the valuable metals contained in battery scrap, i.e. lithium, nickel and, if present, cobalt and manganese. It is another object of the present invention to provide a method to recover further elements, e.g. carbon as graphite and fluorides. It is a further object of the present invention to provide an economical method that reduces the number of expensive and / or energy consuming steps. It is a further object of the present invention to provide a method to recover the transition metals or compounds thereof in high purity, in particular with low contents of copper and precious metals such as Ag, Au and platinum group metals, as well as high purity lithium or compounds thereof with low contents of fluorine and / or phosphorus, or other metallic impurities. Typically, the recovered metals or metal compounds are converted to the corresponding transition metal salts, often sulfates, and lithium carbonate and often lithium hydroxide.

[0014] Known methods for binding fluoride are typically complex and require multiple process steps. It is therefore an object of the present invention to solve the above-mentioned problems of recovering Ni, Co and lithium hydroxide from at least partially reduced black masses containing Ni and / or Co, where at least 10% of Ni and / or Co is present in an oxidation state lower than +2, and also containing lithium salts and fluoride salts, and where the molar ratio of calcium to fluorine is limited to 1.7 or less or to zero. Such black masses are often ferromagnetic. [Means for solving the problem]

[0015] Thus, a method as defined at the outset has been found, hereinafter also referred to as the inventive method or the inventive recycling method, which comprises the steps defined in more detail below, hereinafter also referred to as step (a), step (b), step (c) etc.

[0016] The present invention therefore primarily relates to a method for recovering lithium, as a Li salt, from materials including waste lithium ion batteries or parts thereof, comprising: (a) providing a particulate material containing a transition metal compound and / or transition metal, the transition metal being selected from the group consisting of Mn, Ni and Co, and further wherein at least a portion of the Ni and / or Co, if present, is in an oxidation state lower than +2, and at least a portion of the Mn, if present, is manganese (II) oxide, the particulate material further containing a lithium salt and a fluoride salt, the particulate material optionally containing calcium, with the proviso that the element ratio calcium to fluorine (i.e. molar ratio, mol Ca:mol F) is less than or equal to 1.7 or zero; (b) treating the material provided in step (a) with a polar solvent and an alkaline earth hydroxide; and (c) separating the solid from the liquid, optionally followed by washing the solid residue with a polar solvent, e.g. water. The present invention relates to a method, including [Brief description of the drawings]

[0017] [Figure 1] FIG. 2 is an X-ray powder diffraction pattern (Mo Ka) of reduced mass from waste lithium ion batteries after heating / reduction treatment obtained in Example 1a and used in Example 2a, including reference diffractograms of graphite, cobalt, manganese-II oxide, cobalt oxide, and nickel. [Diagram 2]FIG. 2 is an X-ray powder diffraction pattern (Mo Ka) of the reduced mass from waste lithium ion batteries after heating / reduction treatment obtained in Example 1a and used in Example 2a, including reference diffraction patterns of graphite, lithium aluminate, and lithium carbonate. [Diagram 3] FIG. 2 is an X-ray powder diffraction pattern (Cu Ka) of the reduced mass from waste lithium ion batteries after heating / reduction treatment obtained in Example 1a and used in Example 2a, including reference diffraction patterns of graphite, cobalt, manganese-II oxide, cobalt oxide, and nickel. [Figure 4] FIG. 2 is an X-ray powder diffraction pattern (Cu Ka) of the reduced mass from waste lithium ion batteries after heating / reduction treatment obtained in Example 1a and used in Example 2a, including reference diffraction patterns of graphite, lithium aluminate, and lithium carbonate. [Diagram 5] FIG. 1 is an X-ray powder diffraction pattern (Cu Ka) of LiOH monohydrate obtained in Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The polar solvent used in the present process is typically selected from water, alcohols, ketones, esters, organic carbonates, polyethers, nitriles and mixtures thereof that are capable of dissolving calcium hydroxide as well as water, or even better. Examples of such solvents are glycols, polyols such as glycerol or polyethylene glycol, and mixtures thereof.

[0019] Protic solvents are water, alcohols and mixtures thereof, as described in more detail below. An aqueous medium, e.g., an aqueous solvent or liquid, contains primarily (i.e., 50% by weight (% bw) or more, particularly 80% by weight or more, more particularly 90% by weight or more) water, including water and mixtures of water with one or more alcohols, and may contain additional dissolved substances, so long as the water content, which is critical, is maintained within one or more of the ranges given above.

[0020] Step (b) primarily involves providing a suspension of particulate material in a polar solvent, preferably carried out with heating, the treatment with alkaline earth hydroxide typically being carried out at temperatures in the range of 60-200°C, preferably 70-150°C. Above the boiling point of the polar solvent, the treatment is carried out in the liquid state, under pressure at which the solvent or at least a part of it is maintained. The temperature range around the boiling point of water, i.e. about 70-150°C, is of particular technical importance, in which case the treatment can be achieved at normal pressure or slightly higher pressures (e.g. up to 5 bar) using aqueous liquids or water. Alternatively, this step (b) can also be carried out by application of higher temperatures and pressures, e.g. 150-300°C and 1.5-100 bar.

[0021] The treatment is typically carried out by combining a quantity of alkaline earth hydroxide (AEH) with the particulate material (PM) corresponding to at least 5% of its weight, typically not more than 100%, e.g., 50-1000g AEH per kg PM, preferably 100-1000g AEH, more preferably 200-1000g AEH per kg PM. The amount of polar solvent is typically selected to ensure miscibility of the components, e.g., 0.5-95, preferably about 2.5-21 parts by weight of polar solvent, or in certain cases 1-20, e.g. about 2-10 parts by weight of polar solvent per part by weight of combined solids (PM and AEH).

[0022] In one embodiment of the present invention, step (b) is carried out in a container protected against strong bases, such as molybdenum and copper-rich steel alloys, nickel-based alloys, duplex stainless steel, or glass-lined or enamel- or titanium-coated steel. Further examples are polymer linings and containers made of base-resistant polymers, such as polyethylene, e.g., HDPE and UHMPE, fluorinated polyethylene, perfluoroalkoxyalkanes ("PFA"), polytetrafluoroethylene ("PTFE"), PVdF, and FEP. FEP stands for fluorinated ethylene propylene polymer, i.e., a copolymer of tetrafluoroethylene and hexafluoropropylene.

[0023] The treatment is typically carried out using a mixing device, such as a stirrer, typically applying a power of up to 10 W per kg of suspension, for example 0.5-10 W / kg, and / or circulating with a pump, in order to achieve good mixing and to avoid settling of insoluble components. The shear can be further improved by utilizing baffles. Furthermore, the slurry obtained in step (b) may advantageously be subjected to a grinding treatment, for example in a ball mill or a stirred ball mill, which allows better access of the polar solvent to the finely divided lithium-containing transition metal oxide material. The applied shear and grinding device is typically sufficiently corrosion resistant and can be produced from similar materials and coatings as those mentioned above for the vessel.

[0024] In one embodiment of the present invention, step (b) has a duration in the range of 20 minutes to 24 hours, preferably 1 to 10 hours.

[0025] In one embodiment, step (b) is carried out at least twice, with a solid-liquid separation between each run, until optimal recovery of lithium hydroxide or lithium salt is reached. The resulting lithium salt solutions may be combined or processed separately to recover the solid lithium salt.

[0026] In one embodiment of the invention, steps (b) and (c) are carried out in batch mode. In one embodiment of the invention, steps (b) and (c) are carried out in continuous mode, for example in a cascade of stirred vessels (step b) and / or in a cascade of stirred vessels plus a centrifuge (step c).

[0027] In one embodiment of the present invention, the polar solvent in step (b) is an aqueous medium, and the weight ratio of the aqueous medium to the material prepared in step (a) is in the range of 1:1 to 99:1, preferably 5:1 to 20:1.

[0028] The alkaline earth hydroxide is generally selected from hydroxides of Mg, Ca, Sr and Ba, with calcium hydroxide, barium hydroxide and mixtures thereof being preferred, with calcium hydroxide being most preferred. The alkaline earth hydroxide used in this step (b) may be used as such or may be added in the form of an oxide or a mixture of oxides and hydroxides which will form the alkaline earth hydroxide upon contact with a polar solvent selected from the protic solvents mentioned above.

[0029] The particulate material provided in step (a) typically comprises material obtained from waste lithium ion batteries after a preliminary step (i) of heating under inert or reducing conditions to a temperature in the range of 80-900° C., for example 200-850° C., especially 200-800° C. As explained in more detail below, the preliminary step (i) is typically carried out immediately after discharging, dismantling and / or crushing the lithium ion batteries. In some applications, crushing and / or dismantling is carried out after the preliminary step (i). The lithium ion batteries used, and thus the particulate material provided in step (a), typically contain carbon, for example in the form of graphite.

[0030] For example, for the treatment of a material in this step (i), where an elevated temperature is mentioned, the exposure time, if indicated, defines the total residence time in the reactor or furnace being heated to said elevated temperature, and the temperature of the material should reach a temperature in the given range for at least a fraction of said residence time.

[0031] Unless otherwise specified, "containing" with respect to any substance generally means that such substance is present in an amount still detectable, typically by x-ray powder diffraction, e.g., 1% by weight or more, or that such constituents are present in an amount detectable, typically by ICP after suitable digestion, e.g., 10 ppm by weight or more. The particulate material (PM) provided in this step (a) typically contains, by element, about 1-10% lithium, about 3-30% combinations of transition metal elements, cobalt and / or nickel, and about 4-40% total transition metal elements, including any cobalt, nickel, manganese, copper and iron (all by weight percentages of the dry particulate material provided in step (a)).

[0032] The PM preferably contains nickel and optionally a further transition metal, such as Co.

[0033] In the following, the particulate material provided in step (a) and the material subjected to step (i) are alternatively collectively referred to as a lithium-containing transition metal oxide material.

[0034] Carbon-containing materials may be used as reducing agents in the pretreatment of the reduction described above. Other reducing agents useful for providing a reducing gas stream for this preliminary step (i) are as described in JP 2012-229481, with hydrogen and / or carbon monoxide being preferred. The present invention therefore includes a method comprising the above steps (i) and (a), (b) and (c), wherein the heating step (i) is carried out under reducing conditions comprising the presence of carbon and / or a reducing gas selected from hydrogen, methane and carbon monoxide.

[0035] Step (i) Method 1 When hydrogen is used as the reducing gas, the preliminary step (i) is preferably carried out as follows: (i) a lithium-containing transition metal oxide material originating from a lithium ion battery and containing fluorine compounds and / or phosphorus compounds as impurities is heated in the presence of H2 to a temperature in the range of 200-900°C or as indicated above.

[0036] Typically, the lithium-containing transition metal oxide material heated in step (i) originates from a lithium ion battery and preferably contains fluorine in the range of 1% by weight to 8% by weight, and / or phosphorus in the range of 0.2% by weight to 2% by weight, based on the weight of the lithium-containing transition metal oxide material.

[0037] Step (i), which is carried out using hydrogen, involves heating the lithium-containing transition metal oxide material to a temperature in the range of 200 to 900 °C, preferably 300 to 600 °C, more preferably 350 to 500 °C. It is generally preferred not to expose the lithium-containing transition metal oxide material to temperatures above 500 °C, since strong heating, especially under oxidizing conditions and to a lesser extent also under reducing atmospheres, tends to increase the formation of insoluble species (e.g. LiMnO2). As a result, it is preferred to keep the temperature below 500 °C even in step (i), and in one embodiment of the method, step (i) is carried out using hydrogen at a temperature in the range of 350 to 450 °C, for example 380 to 450 °C, in particular 380 to 440 °C. The atmosphere used to carry out the reduction contains, according to this embodiment, 0.1 vol. % to 100 vol. % hydrogen, the remainder being a non-oxidizing gas, preferably nitrogen, argon, water vapor, carbon monoxide, carbon dioxide, or a mixture of at least two of these gases. Preferred non-oxidizing gases are nitrogen and water vapor, and mixtures of nitrogen and water vapor. In a preferred embodiment, step (i) of the process is carried out mainly under hydrogen, for example in an atmosphere containing 35-100% by volume, preferably 50-100% by volume (normal conditions) of hydrogen, the remainder being non-oxidizing gas, if any. In this embodiment of the invention, step (i) has a duration (residence time) in the range of 10 minutes to 30 hours, preferably 20 minutes to 8 hours, more preferably 30 minutes to 4 hours. The duration of step (i), preferably in the presence of hydrogen, lasting 20 to 90 minutes, is of special technical interest.

[0038] The concentration of hydrogen in the reducing atmosphere and the reaction time are interdependent: usually, a lower concentration of hydrogen requires a longer reduction time and vice versa.

[0039] Thus, in a preferred method of the invention, step (i) is carried out by heating the lithium-containing transition metal oxide material to a temperature in the range of 350-450° C. in the presence of more than 35% by volume, particularly 50-100% by volume, of H2 for a period of 20-90 minutes. Within the present invention, a particularly preferred method is to carry out step (i) at a temperature between 400° C. and 450° C., for example between 400° C. and 420° C., for up to 2.5 hours using 35% by volume or more of hydrogen, in order to recover Li in a particularly efficient manner in step (b), although applying a temperature that is too high may result in a low yield, and a long duration, although without any negative effects, tends to reduce the space-time yield, and a H2 concentration of 35% by volume or more is preferred as it leads to a short reaction time of 2.5 hours or less, and an optimal space-time yield can be achieved using more than 80% by volume of hydrogen.

[0040] After the heat treatment, the material is transferred from the oven to a cooling unit. Here, the material is cooled, preferably to a temperature below 100°C. Cooling can be performed at ambient conditions, for example by storing the hot material in a chamber or container or in a rotating tube, which may be the last unheated or cooled part of a rotary kiln, where the heat treatment is performed and the heat can be transferred to the environment. Preferably, the hot material can be cooled and conveyed by a cooling conveying screw. A more rapid cooling can be obtained by introducing a gas, which can be fed to the heat exchanger after passing through the hot material bed. Such gas cooling can be designed as a fixed bed, a moving bed or a fluidized bed. The gas used is preferably an inert gas, such as nitrogen, argon or carbon dioxide. It is also possible to use a reducing gas, which is preferably used for reduction at the beginning of the cooling period, when the material is still at a temperature close to the oven temperature. Afterwards, the gas composition can be changed to an inert gas at a lower temperature, or even an oxygen-containing gas, such as air, or a mixture of air and an inert gas can be used.

[0041] Alternatively, the hot material can be quenched with a liquid for cooling under dry conditions in a gas atmosphere. Quenching can be carried out by spraying the hot material with a cooling liquid, either in an amount where the liquid evaporates and the material remains essentially dry (evaporative cooling), or in a larger amount where a slurry of the material is formed. Cooling with a liquid is particularly preferred when the resulting cooled material or slurry can be used directly for step (b) of the invention. Thus, the preferred quench liquid is a sufficiently temperature stable polar solvent, with water being most preferred. The liquid can be pumped through a heat exchanger and recycled back to the cooling vessel.

[0042] Step (i) Method 2 When using a carbon-based material, such as carbon, as the reducing agent, the preliminary step (i) is preferably carried out as follows: (i) heating the lithium-containing transition metal oxide material in the presence of the carbon-based material, such as carbon, for example in the presence of graphite, to a temperature in the range of 200 to 900° C. In a preferred embodiment of the present invention, graphite contained in the black mass is used as the reducing agent.

[0043] As explained in more detail below, typically the lithium-containing transition metal oxide material heated in step (i) originates from a lithium ion battery and may contain typical impurities such as fluorine.

[0044] Step (i), which is carried out using a carbon-based material, such as carbon, as a reducing agent, comprises heating the lithium-containing transition metal oxide material to a temperature in the range of 200 to 900°C, preferably 300 to 850°C, more preferably 500 to 850°C.

[0045] The atmosphere used to carry out the reduction, according to this embodiment, either does not contain oxygen or contains up to 20% by volume of oxygen, the remainder being a non-oxidizing gas, preferably nitrogen, argon, water vapor, carbon monoxide, carbon dioxide or a mixture of at least two of these gases. Preferred non-oxidizing gases are nitrogen and carbon monoxide, and mixtures of nitrogen and carbon monoxide. In a preferred embodiment, step (i) of the process is carried out under air or diluted air, for example in an atmosphere containing 1 to 20% by volume, preferably 1 to 10% by volume of oxygen (normal conditions), the remainder being a non-oxidizing gas, if present. In this embodiment of the invention, step (i) has a duration in the range of 10 minutes to 30 hours, preferably 20 minutes to 8 hours, more preferably 30 minutes to 4 hours. The duration of step (i), preferably in the presence of carbon, lasting 20 to 120 minutes, especially 30 to 120 minutes, is of special technical interest.

[0046] After the heat treatment, the material is transferred from the oven to a cooling unit. Here, the material is cooled, preferably to a temperature below 100°C. Cooling can be performed at ambient conditions, for example by storing the hot material in a chamber or container or in a rotating tube, which may be the last unheated or cooled part of a rotary kiln, where the heat treatment is performed and the heat can be transferred to the environment. Preferably, the hot material can be cooled and conveyed by a cooling conveying screw. A more rapid cooling can be obtained by introducing a gas, which can be fed to the heat exchanger after passing through the hot material bed. Such gas cooling can be designed as a fixed bed, a moving bed or a fluidized bed. The gas used is preferably an inert gas, such as nitrogen, argon or carbon dioxide. It is also possible to use a reducing gas, which is preferably used for reduction at the beginning of the cooling period, when the material is still at a temperature close to the oven temperature. Afterwards, the gas composition can be changed to an inert gas at a lower temperature, or even an oxygen-containing gas, such as air, or a mixture of air and an inert gas can be used.

[0047] Alternatively, the hot material can be quenched with a liquid for cooling under dry conditions in a gas atmosphere. Quenching can be carried out by spraying the hot material with a cooling liquid, either in an amount where the liquid evaporates and the material remains essentially dry (evaporative cooling), or in a larger amount where a slurry of the material is formed. Cooling with a liquid is particularly preferred when the resulting cooled material or slurry can be used directly for step (b) of the invention. Thus, the preferred quench liquid is a sufficiently temperature stable polar solvent, with water being most preferred. The liquid can be pumped through a heat exchanger and recycled back to the cooling vessel.

[0048] In one embodiment of the present invention, the reduction conditions relate to hydrogen and / or carbon / oxygen concentrations, and the temperature and duration of step (i) are selected such that at least a portion of the lithium-containing transition metal oxide material contains paramagnetic, antiferromagnetic, ferromagnetic and / or ferrimagnetic components. The formation of ferromagnetic or ferrimagnetic components resulting from at least partial reduction of the lithium-containing transition metal material is preferred. The degree of reduction can vary in the range of 1-100% with respect to the nickel contained in the lithium-containing transition metal material, but is preferably in the range of 80-100%.

[0049] Thus, the particulate material provided in step (a) contains a transition metal compound and / or a transition metal selected from the group consisting of Mn, Ni and / or Co, and further wherein at least a portion of the Ni and / or Co, if present, is in an oxidation state lower than +2, and wherein at least a portion of the Mn, if present, is manganese (II) oxide, in which the nickel and / or cobalt is typically, at least in part, present in the metallic state.

[0050] The presence of phases in oxidation states lower than +2, such as Ni and / or Co, Mn in the form of manganese(II) oxide, and nickel and / or cobalt as metal, can be detected by XRD, as described further below.

[0051] The lithium and fluoride salts present in the particulate material prepared in step (a) are detected by standard methods described below. The lithium and fluoride salts contained in the particulate material prepared in step (a) typically include one or more salts of LiOH, LiF, Li2O, Li2CO3, LiHCO3, lithium aluminate, lithium phosphate salts, mixed oxides of Li with one or more of Ni, Co, Mn, Fe, Al, Cu, and / or fluorides of Ni, Co, Mn, Fe, Al, Cu. LiOH, LiF, Li2O, Li2CO3, LiHCO3, lithium aluminate, and lithium phosphate typically account for 95% or more by weight of the total lithium salts present. LiF, Li2CO3, LiOH, and lithium aluminate are very often present. A larger proportion of fluoride, for example 50% or more by weight, is typically present as lithium fluoride. The fluoride salts present typically come in part from the electrolyte salts and polymeric binders of the former battery, hydrogen fluoride is liberated during preliminary steps of discharging or dismantling or drying the battery materials, and other types of fluoride salts resulting from the rapid reaction of hydrogen fluoride with the former cell or electrode materials, such as cobalt fluoride, may be present as well.

[0052] The particulate material prepared in step (a) is generally a material originating from a lithium ion battery or a part of a lithium ion battery, in particular a cell material thereof. For step (a), the material is prepared in the form of a dry powder, a wet powder or a suspension of particles in a liquid. The material typically has an average particle diameter (D50 according to ISO 13320 EN:2009-10) in the range of 1 μm to about 2 mm, in particular 1 μm to 1 mm. In a typical method, an upper limit on the size of the particles in the powder material is given by a sieving step performed before step (a) or even before step (i), for example using a sieve that allows particles of up to 2 mm, in particular up to 1 mm, to pass through the mesh.

[0053] Typically, the lithium-containing transition metal oxide material is obtained after mechanically removing the casing, wiring or circuitry, and therefore typically consists mainly of cell material. For safety reasons, such lithium-ion batteries are fully discharged or electrically discharged at least 80% (preferably more than 90%, most preferably more than 95%), for example by immersion in a dry conductive bath, for example metal strips, so that residual electrical energy can be recovered, which otherwise may cause short circuits that constitute a fire and explosion hazard. Such lithium-ion batteries can be disassembled, punched, crushed, for example in a hammer mill, or crushed, for example in an industrial shredder. Although not preferred, the batteries can also be discharged by immersing them in a conductive liquid, for example an aqueous solution of a metal salt, such as sodium sulfate. Crushing can also be carried out in a liquid, preferably in water. This has the advantage of preventing dust formation and the creation of an ignitable atmosphere.

[0054] Before subjecting the material to the preliminary step (i), it may be advantageous to at least partially remove the electrolyte, in particular the electrolyte comprising an organic solvent or a mixture of organic solvents, for example by drying at subatmospheric pressure, for example at a temperature in the range of 50-250° C. As mentioned above, the lithium-containing transition metal oxide material is preferably not exposed to high temperatures (in particular above 400° C.) under oxidizing conditions before being subjected to this step (a).

[0055] In one embodiment of the present invention, the lithium-containing transition metal oxide material is derived from battery scrap. In a preferred embodiment of the present invention, the lithium-containing transition metal oxide material is derived from mechanically treated battery scrap, for example, battery scrap treated in a hammer mill or industrial shredder. This mechanical treatment can be carried out under dry or wet conditions, preferably in the presence of water.

[0056] In one embodiment of the invention, step (a) is preceded by step (a1), which step (a1) comprises, for example, removing carbon or organic polymers by a solid-solid separation method. Examples of such solid-solid separation methods are electric sorting, sieving, magnetic separation, flotation or other classification methods. Solid-solid separation can be carried out dry or in the presence of a suitable carrier medium, preferably water.

[0057] In one embodiment of the present invention, the mechanically treated battery scrap is ground prior to step (a). Such grinding is preferably carried out in a ball mill or an agitated ball mill. Milling can be carried out under wet or dry conditions, with dry conditions being preferred.

[0058] In one embodiment of the present invention, prior to step (a), the mechanically treated battery scrap is contacted with water and / or an organic solvent, followed by a solid-liquid separation step.

[0059] In one embodiment, the mechanically treated battery scrap is contacted with a basic or acidic solution to facilitate the peeling of the active material from the electrode foil, as described in WO 2018 / 192122.

[0060] In one embodiment of the present invention, prior to the thermal treatment of step (i), the mechanically treated battery scrap is subjected to a solvent treatment in order to dissolve and separate the polymeric binder used to bind the lithium transition metal oxide to the current collector film. Suitable solvents are N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide and N-ethylpyrrolidone, dimethylsulfoxide, hexamethyl phoshoramide, tetramethylurea, trimethylphosphate and triethylphosphate, in pure form or as a mixture.

[0061] The solvent treatment can be carried out with one or more solvents in successive steps or in one step utilizing a solvent capable of dissolving the electrolyte components and the binder polymer. The solvent is applied in a temperature range of 10° C. to 200° C. In particular, dissolution of the polymer may require elevated temperatures ranging from 50 to 200° C., preferably between 100° C. and 150° C. The upper temperature limit is usually limited by the boiling point of the solvent, unless pressures higher than 1 bar are applied.

[0062] In one embodiment, washing of the mechanically treated battery scrap is carried out with an aprotic solvent in the absence of moisture, for example under a dry gas such as dry air, dry nitrogen.

[0063] In one embodiment of the present invention, the lithium-containing transition metal oxide material contains not only battery scrap material, but also off-spec material, including parts or materials from parts of lithium-ion batteries, such as pure electrode materials. However, the lithium-containing transition metal oxide material preferably contains compounds other than nickel compounds, such as nickel / cobalt components, or nickel / cobalt / manganese or nickel / cobalt / aluminum compounds, in the range of 0.1 to 80% by weight, if applicable, and in extreme cases, valuable materials are the minority components. Examples of such components are electrically conductive forms of carbon, hereinafter also referred to as conductive carbon, such as graphite, soot and graphene. Further examples of impurities are copper and its compounds, aluminum and aluminum compounds, such as alumina, iron and iron compounds, zinc and zinc compounds, silicon and silicon compounds, such as silica and silicon oxide SiO. y[Zero < y ≤ 2], tin, silicon-tin alloys, and organic polymers such as polyethylene, polypropylene, and fluorinated polymers such as polyvinylidene fluoride, tetrafluoroethylene polymers, etc. Further impurities may be fluorine compounds such as inorganic fluorides, and phosphorus compounds that may be derived from liquid electrolytes, such as widely used LiPF6 and impurities in the products derived from the hydrolysis of LiPF6. The battery scrap serving as the starting material for the method of the present invention may be derived from multiple sources. Therefore, in the majority of embodiments, the lithium-containing transition metal oxide material contains, when applicable, nickel / cobalt compounds, or compounds other than nickel / cobalt / manganese or nickel / cobalt / aluminum components. One such component is carbon in an electrically conductive form within the range of 2 to 65% by weight with respect to the entire lithium-containing transition metal oxide material.

[0064] In typical embodiments of the present invention, the lithium-containing transition metal oxide material contains one or more of the following additional components or impurities: i) Copper in the form of one or more of a metal or its compounds within the range of 20 ppm by weight to 10% by weight, especially within the range of 20 ppm by weight to 3% by weight, ii) Aluminum in the form of one or more of a metal or its compounds within the range of 100 ppm by weight to 15% by weight, iii) Iron in the form of a metal or alloy or one or more of its compounds within the range of 100 ppm by weight to 5% by weight, iv) Zinc in the form of a metal or alloy or one or more of its compounds within the range of 20 ppm by weight to 2% by weight, v) Zirconium in the form of a metal or alloy or one or more of its compounds within the range of 20 ppm by weight to 2% by weight, vi) Fluorine calculated as the sum of organic fluorine bonded to a polymer, for example, and inorganic fluoride in one or more inorganic fluorides, within the range of 1% by weight to 8% by weight, especially within the range of 2% by weight to 8% by weight, vii) Phosphorus that may appear in one or more inorganic compounds within the range of 0.2% by weight to 2% by weight, viii) Manganese in the form of one or more of the metal or its compounds, in the range of 100 ppm by weight to 15% by weight.

[0065] Examples of such embodiments include one or two of the above additional components, or additional components (i), (ii) and (iii); (i), (ii) and (iv); (i), (ii) and (v); (i), (ii) and (vi); (i), (ii) and (viii); (i), (iii) and (iv); (i), (iii) and (v); (i), (iii) and (vi); (i), (iii) and (vii); (i), (iii) and (viii); (i), (iv) and (v); (i), (iv) and (vi); (i), (iv) and (vii); (i), (iv) and (viii); (i), (v) and (vi); (i), (v) and (vii); (i), (iv) and (viii); (i), (v) and (vi); (i), (v) and (vii); (i), (v) and (vii); (i), (v) and (vii); (i), (v) and (vii); (i), (v) and (vii); (i), (v) and (vii); (i), (v) and (vii); (i), (v) and (vii); (i), (vii) and (viii); (i), (ii), (iii) and (iv); (i), (ii), (iii) and (v); (i), (ii), (iii) and (vi); (i), (ii), (iii) and (vii); (i), (ii), (iii) and (viii); (i), (ii), (iv) and (v); (i), (ii), (iv) and (vi); (i), (ii), (iv) and (vii); (i), (ii), (iv) and (viii); (i), (ii), (v) and (vi); (i), (ii), (v) and (vii); (i), (ii), (v) and (viii); (i), (ii), (v) and (vii); (i), (ii), (v) and (viii); (i), (ii), (vi) and (vii); (i), (ii), (vi) and (viii); (i), (ii), (vii) and (viii); (i), (iii), (iv) and (v); (i), (iii), (iv) and (vi); (i), (iii), (iv) and (vii); (i), (iii), (iv) and (viii); (i), (iii), (v) and (vi); (i), (iii), (v) and (vii); (i), (iii), (v) and (viii); (i), (iii), (vi) and (vii); (i), (iii), (vi) and (vii); (i), (iii), (vi) and (viii); (i), (iii), (vii) and (viii); (i), (iii), (vii) and (viii); (i), (iv), (v) and (vii); (i), (iv), (v) and (vii); (i), (iv), (v) and (viii);(i), (iv), (vi) and (vii); (i), (iv), (vi) and (viii); (i), (iv), (vii) and (viii); (i), (v), (vi) and (vii); (i), (v), (vi) and (viii); (i), (v), (vii) and (viii); (i), (vi), (vii) and (viii); (i), (vi), (vii) and (viii); (ii), (iii), (iv) and (v); (ii), (iii), (iv) and (vii); (ii), (iii), (iv) and (vii); (ii), (iii), (iv) and (viii); (ii), (iii), (v) and (vi); (ii), (iii), (v) and (vii); (ii), (iii), (iv) and (viii); (ii), (iii), (v) and (vi); (ii), (iii), (v) and (vii); (ii), (iii), (v) and (vii); (ii), (iii), (v) and (vii); (ii), (iii), (v) and (viii); (ii), (iii), (vi) and (vii); (ii), (iii), (vi) and (viii); (ii), (iii), (vii) and (viii); (ii), (iv), (v) and (vi); (ii), (iv), (v) and (vii); (ii), (iv), (v) and (viii); (ii), (iv), (vi) and (vii); (ii), (iv), (v) and (viii); (ii), (iv), (vii) and (vii); (ii), (iv), (vi) and (viii); (ii), (iv), (vii) and (viii); (ii), (v), (vii) and (vii); (ii), (v), (vii) and (viii); (ii), (vi), (vii) and (viii); (ii), (vi), (vii) and (viii); (iii), (iv), (v) and (vi); (iii), (iv), (v) and (vii); (iii), (iv), (v) and (viii); (iii), (iv), (vi) and (vii); (iii), (iv), (vi) and (viii); (iii), (iv), (vii) and (viii); (iii), (v), (vi) and (vii); (iii), (v), (vi) and (viii); (iii), (v), (vii) and (viii); (iii), (v), (vii) and (viii); (iii), (vi), (vii) and (viii); (iii), (vi), (vii) and (viii); (iv), (v), (vi) and (vii); (iv), (v), (vi) and (viii); (iv), (v), (vii) and (viii); (iv), (vi), (vii) and (viii); (iv), (vi), (vii) and (viii); (v), (vii) and (viii);(i), (ii), (iii), (iv) and (v); (i), (ii), (iii), (iv) and (vi); (i), (ii), (iii), (iv) and (vii); (i), (ii), (iii), (iv) and (viii); (i), (ii), (iii), (iii), (v) and (vii); (i), (ii), (iii), (v) and (viii); (i), (ii), (iii), (iii), (vi) and (vii); (i), (ii), (iii), (iii), (vi) and (viii); (i), (ii), (iii), (iii), (vi) and (vii); (i), (ii), (iii), (iii), (vi) and (viii); (i), (ii), (iii), (iii), (vii) and (viii); (i), (ii), (iii), (iv), (v) and (vii); (i), (ii), (iv), (v) and (viii); (i), (ii), (iv), (vi) and (vii); (i), (ii), (iv), (vi) and (viii); (i), (ii), (iv), (vii) and (viii); (i), (ii), (v), (vi) and (vii); (i), (ii), (v), (vi) and (vii); (i), (ii), (v), (vii) and (viii); (i), (ii), (v), (vii) and (viii); (i), (ii), (vi), (vii) and (viii); (i), (iii), (iv), (v) and (vi); (i), (iii), (iv), (v) and (vii); (i), (iii), (iv), (v) and (vii); (i), (iii), (iv), (v) and (vii); (i), (iii), (iv), (v) and (viii); (i), (iii), (iv), (vi) and (vii); (i), (iii), (iv), (vi) and (viii); (i), (iii), (iv), (vii) and (viii); (i), (iii), (v), (vi) and (vii); (i), (iii), (v), (vi) and (viii); (i), (iii), (vi), (vii) and (viii); (i), (iv), (v), (vii) and (vii); (i), (iv), (v), (vi), (vii) and (vii); (i), (iv), (v), (vi), (vii) and (viii); (i), (iv), (v), (vii) and (viii); (i), (iv), (vi), (vii) and (viii); (i), (v), (vii) and (vii); (i), (v), (vii), (vii) and (viii); (ii), (iii), (iv), (v) and (vii);(ii), (iii), (iv), (v) and (viii); (ii), (iii), (iv), (vi) and (vii); (ii), (iii), (iv), (vi) and (viii); (ii), (iii), (iv), (vii) and (viii); (ii), (iii), (v), (vi) and (vii); (ii), (iii), (v), (vi) and (viii); (ii), (iii), (v), (vii) and (viii); (ii), (iii), (vi), (vii) and (viii); (ii), (iv), (v), (vi) and (vii); (ii), (iv), (v), (vi) and (viii); (ii), (iv), (v), (vii) and (viii); (ii), (iv), (vi), (vii) and (viii); (ii), (v), (vi), (vii) and (viii); (iii), (iv), (v), (vi) and (vii); (iii), (iv), (v), (vi) and (viii); (iii), (iv), (v), (vii) and (viii); (iii), (iv), (vi), (vii) and (viii); (iii), (v), (vi), (vii) and (viii); (iv), (v), (vi), (vii) and (viii); (i), (ii), (iii), (iv), (v) and (vi); (i), (ii), (iii), (iv), (v) and (vii); (i), (ii), (iii), (iv), (v) and (viii); (i), (ii), (iii), (iv), (vi) and (vii); (i), (ii), (iii), (iv), (vi) and (viii); (i), (ii), (iii), (iv), (vii) and (viii); (i), (ii), (iii), (v), (vi) and (vii); (i), (ii), (iii), (v), (vi) and (viii); (i), (ii), (iii), (v), (vii) and (viii); (i), (ii), (iii), (vi), (vii) and (viii); (i), (ii), (iv), (v), (vi) and (vii); (i), (ii), (iv), (v), (vi) and (viii); (i), (ii), (iv), (v), (vii) and (viii);(i), (ii), (iv), (vi), (vii) and (viii); (i), (ii), (v), (vi), (vii) and (viii); (i), (iii), (iv), (v), (vi) and (vii); (i), (iii), (iv), (v), (vi) and (viii); (i), (iii), (iv), (v), (vii) and (viii); (i), (iii), (iv), (vi), (vii) and (viii); (i), (iii), (v), (vi), (vii) and (viii); (ii), (iii), (iv), (v), (vi) and (vii); (ii), (iii), (iv), (v), (vi) and (viii); (ii), (iii), (iv), (v), (vii) and (viii); (ii), (iii), (iv), (vi), (vii) and (viii); (ii), (iii), (v), (vi), (vii) and (viii); (ii), (iv), (v), (vi), (vii) and (viii); (iii), (iv), (v), (vi), (vii) and (viii); (i), (ii), (iii), (iv), (v), (vi) and (vii); (i), (ii), (iii), (iv), (v), (vi) and (viii); (i), (ii), (iii), (iv), (v), (vii) and (viii); (i), (ii), (iii), (iv), (vi), (vii) and (viii); (i), (ii), (iii), (v), (vi), (vii) and (viii); (i), (ii), (iv), (v), (vi), (vii) and (viii); (i), (iii), (iv), (v), (vi), (vii) and (viii); (ii), (iii), (iv), (v), (vi), (vii) and (viii). Another example is a lithium-containing transition metal oxide material containing each of the above additional components;

[0066] Each of the percentages given above is by weight of the dry material (ie, the lithium-containing transition metal oxide material provided in this step (a)).

[0067] The lithium-containing transition metal oxide material typically contains nickel or cobalt, or especially both nickel and cobalt. Examples of lithium-containing transition metal oxide materials may be based on lithiated nickel cobalt manganese oxide ("NCM") or lithiated nickel cobalt aluminum oxide ("NCA"), or mixtures thereof.

[0068] Examples of layered nickel-cobalt-manganese oxides are those of the general formula Li 1+x (Ni a Co b Mn c M 1 d ) 1-x O2 compound, M 1 is selected from Mg, Ca, Ba, Al, Ti, Zr, Zn, Mo, V and Fe, and further variables are defined as follows: Zero≦x≦0.2 0.1≦a≦0.95, Zero ≦ b ≦ 0.9, preferably 0.05 <b≦0.5、 zero ≦ c ≦ 0.6, Zero≦d≦0.1 and a+b+c+d=1.

[0069] In a preferred embodiment, in the compound according to general formula (I), Li (1+x) [Ni a Co b Mn c M 1 d ] (1-x) O2(I) M 1 is selected from Ca, Mg, Zr, Al, Ti and Ba; Further variables are defined as above.

[0070] An example of a lithium nickel-cobalt aluminum oxide is represented by the general formula Li[Ni h Co i Al j ]O 2+rTypical values ​​for r, h, i and j are: h is in the range of 0.8 to 0.95, i is in the range of 0.02 to 0.3, j is in the range of 0.01 to 0.10, r is in the range of zero to 0.4.

[0071] Li (1+x) [Ni 0.33 Co 0.33 Mn 0.33 ] (1-x) O2, Li (1+x) [Ni 0.5 Co 0.2 Mn 0.3 ] (1-x) O2, Li (1+x) [Ni 0.6 Co 0.2 Mn 0.2 ] (1-x) O2, Li (1+x) [Ni 0.7 Co 0.2 Mn 0.1 ] (1-x) O2, Li (1+x) [Ni 0.8 Co 0.1 Mn 0.1 ] (1-x) O2 (wherein x is as defined above), and Li[Ni 0.85 Co 0.13 Al 0.02 ]O2 is particularly preferred.

[0072] The lithium-containing transition metal oxide material may have a regular shape, but usually has an irregular shape. However, it is preferable to remove light parts, such as organic plastic housing parts and aluminum or copper foil, as much as possible, for example in a forced gas flow.

[0073] In one embodiment, the composition of the atmosphere is changed during step (i), which may be done before switching the atmosphere to a reducing atmosphere, such as a hydrogen-containing atmosphere, for example if volatile organic compounds are present in the feed which are stripped in the inert atmosphere.

[0074] In one embodiment, an oxidizing atmosphere in the temperature range of 20-300° C. is used in step (i) prior to reduction with a hydrogen-containing atmosphere. This embodiment allows some impurity components, i.e. organic components, to be combusted or the material to be dried (among other things, as further described above, temperatures of up to 250° C. are utilized. The preferred oxidizing gas is oxygen or an oxygen-containing gas, such as air. Materials originating from spent lithium-ion battery cells, containing lithium, transition metal oxides, and also fluorine and / or phosphorus compounds, are preferably not subjected to oxidation above 300° C. prior to carrying out the steps of the method.

[0075] In one embodiment of the invention, step (a) is preceded by step (a1), which comprises, for example, removing carbon or organic polymers by a dry solid-solid separation method. Examples of such dry solid-solid separation methods are electric sorting, sieving, magnetic separation or other classification methods, where step (a1) is introduced as an additional step.

[0076] In one embodiment of the present invention, the material provided in step (a) is ground prior to step (b) in order to deagglomerate the different solid particles from one another, if they are somewhat agglomerated, for example by residual binder polymer. The grinding can be carried out under dry or wet conditions. Preferably, the grinding is carried out in an aqueous medium which is also utilized in the subsequent step (b).

[0077] At the end of step (b), the pressure may be released if applicable. A solution of lithium salt is obtained from step (c) as a liquid, typically an aqueous solution containing LiOH.

[0078] Prior to this step (c), the solid residue is contained in a polar solvent, which may be an aqueous solution, to form a suspension. If the extraction of the Li-compound is carried out in two or more steps as described above, the solid residue will be contained in the slurry of the second or last step, respectively.

[0079] The solid residue obtained in step (c) is recovered by a solid-liquid separation step (c), which may be a type of filtration or centrifugation, or settling and decantation, optionally followed by a washing step, in which the respective polar solvent used as washing medium in step (b) is applied. The filtrate and the washing liquid are usually combined before recovering the lithium salt. To recover such solid material, which contains fine particles, for example with an average diameter of 50 μm or less, a flocculating agent, for example a polyacrylate, may be added.

[0080] The solid residue obtained by step (c) is characterized by a typical elemental composition resulting from the application of the preferred process conditions during step (b). In particular, the solid residue is characterized by a composition typical of battery scrap material (Li, graphite and at least one of Ni, Co, Mn present), but with a significantly higher (Ni + Co + Mn) to Li weight ratio. Since battery scrap material, especially the cathode active material, is characterized by a (Ni + Co + Mn):Li weight ratio between 5 and 12, the solid residue after step (c) is characterized by a lower Li content, and therefore a (Ni + Co + Mn):Li weight ratio between 13 and 100000. Furthermore, the preferred process in step (b) is accompanied by a significant increase in the calcium content, which, as mentioned above, is very low (0-0.5 wt%) in the initial particulate material prepared in step (a). The solid residue obtained by step (c) is characterized by an elemental Ca weight content of between 2% and 50% (based on the dry solids).

[0081] This solid residue obtainable by step (c) is a source of valuable materials useful for the production of new batteries, and steps for the isolation of such materials are described below.

[0082] The solid residue obtained by step (c) may subsequently be subjected to step (d), a solid-solid separation to recover Ni and / or Co, if present. By carrying out step (d), nickel is recovered as a nickel-containing solid.

[0083] Step (d) of the present invention comprises a solid-solid separation step. In a preferred embodiment, this step is a wet solid-solid separation step. This solid-solid separation step serves to separate insoluble components such as carbon and polymers, or insoluble inorganic components, such as metal or metal oxide particles, from the metal or metal oxide components of the lithium-containing transition metal oxide material. After the solid-solid separation of step (d), a solid concentrate fraction is obtained, which contains Ni and, where applicable, most of the Co in concentrated form. Such a solid-solid separation step can be carried out mechanically, by column or pneumatic means, or by combined flotation. In many embodiments, collector compounds are added to the slurry to make the target components hydrophobic. Typical collector compounds for carbon and polymer particles are hydrocarbons or fatty alcohols, which are introduced in amounts of 1 g to 50 kg per ton of solid residue obtained from step (c). Flotation can also be carried out in the opposite sense, i.e. by converting the originally hydrophilic components into strongly hydrophobic ones by special collectors, e.g. fatty alcohol sulfates or esterquats. Direct flotation using hydrocarbon collectors, e.g. mineral oil, kerosene or diesel oil, is preferred. In order to improve the selectivity of the flotation towards carbon and polymer particles, inhibitors can also be added, which reduce the amount of metal and metal oxide components entrained in the foam phase. Agents that can be used can be acids or bases to control the pH value within the range of 3 to 9. They can also be ionic components, e.g. sodium silicate, which adsorb to the metal or metal oxide surfaces, or bipolar components, e.g. amino acids. To increase the efficiency of the flotation, it can be advantageous to add carrier particles, e.g. polymer particles, carbonaceous particles, e.g. graphite or coal, which form agglomerates with the hydrophobic target particles. By using magnetic carrier particles, magnetic agglomerates can be formed which can be separated magnetically.If the target components are paramagnetic, antiferromagnetic, ferrimagnetic, or ferromagnetic, they can also be separated by magnetic separation using high-intensity magnetic separators ("WHIMS"), medium-intensity magnetic separators ("MIMS"), or low-intensity magnetic separators ("LIMS"). Other solid-solid separation techniques use density differences of solid components, for example the density difference between graphite and metals or metal oxides. These techniques include sink-float methods, which utilize a fluid of intermediate density to that of the solid components to be separated. Another technique in this class is heavy liquid separation. Further separation techniques based on density differences are spirals and hydrocyclones.

[0084] Combinations of at least two of the aforementioned solid-solid separation techniques may also be utilized. These combinations may include roughing, cleaning and cleaning steps typical of mineral processing flowsheets.

[0085] In a preferred embodiment, the solid-solid separation in step (d) is magnetic separation.

[0086] In one embodiment of the present invention, the solid material resulting from step (c) is ground prior to step (d) in order to free the different solid particles from one another if they are somewhat agglomerated, for example by residual binder polymer. Such grinding is preferably carried out in a ball mill or stirred ball mill.

[0087] In one embodiment of the present invention, step (d) is a wet solid-solid separation utilizing an aqueous medium, preferably water, as the fluid. The weight ratio of the fluid medium to the solid material in such step (d) is typically in the range of 1:1 to 99:1, preferably 2:1 to 9:1.

[0088] The wet solid-solid separation of step (d) results in two slurries: one containing the target transition metal-containing solid material and the other containing other components such as carbonaceous materials and polymers, and, if applicable, also some inorganic compounds. By suitable selection and, if necessary, combination of solid-solid separation steps, at least 60% of the Ni and, if present, Co are obtained and concentrated in one fraction. Preferably, at least 80-99% of the Ni and, if present, Co are separated.

[0089] In one embodiment of the invention, the liquid phase of the slurry fed to step (d) contains dissolved lithium. In this case, one or the other or both slurries resulting from the solid-solid separation in step (d) are advantageously subjected to solid-liquid separation to recover the lithium solution. The lithium solution may then be further processed in step (e).

[0090] In step (e), the lithium-containing solution resulting from any of the steps described above, such as step (c) and / or step (d), is treated to recover lithium in the form of a solid material, either as a hydroxide or a salt.

[0091] In one embodiment of the present invention, the Li salt, in particular LiOH, is recovered by evaporation of the water contained in the solution (e1), which may be carried out in two or more successive steps (e2 and e3 for example) to produce the Li salt of the desired high purity.

[0092] First, the Li-containing solution from any of the above steps is concentrated to near the point where the solubility limit of LiOH is reached. This step involves solid formation (e.g., crystallization) of impurities with lower solubility than LiOH, possible impurities can be, but are not limited to, Ca(OH)2, CaF2, CaCO3, LiF. These are separated by solid-liquid separation, e.g., filtration or centrifugation, or a type of settling and decantation. Also a combination of two solid-liquid separation steps is possible, e.g., a hydrocyclone followed by a depth filter, since there is less remaining solid to separate. If LiF precipitates during this first concentration step (e2), it is preferable to re-feed the solid material to step (b).

[0093] The filtrate obtained from the solid-liquid separation after one of the concentration steps, i.e. the concentrated LiOH solution, is then used for the next evaporation step (e3). High quality LiOH can be obtained by evaporating the remaining water and forming a LiOH solid. In case of crystallization, the crystals are again separated from the remaining mother liquor by solid-liquid separation and optionally washed. To concentrate the impurities, multiple crystallization steps followed by washing and solid-liquid separation are possible.

[0094] Any mother liquor obtained from the crystallization may be subjected to further steps such as evaporation, crystallization, separation (e.g. ion exchange) and / or recycled by introducing the mother liquor into step (b) or (e1) or (e2).

[0095] All of the above solidification steps are advantageously followed by drying of the solid. Drying either below 60° C. or at higher temperatures under humid conditions results in LiOH monohydrate, otherwise at least partially anhydrous LiOH is obtained.

[0096] In that case, according to the described step (e1), the filtrate obtained after step (c) is dried by total evaporation of a polar solvent, for example water, to obtain LiOH (anhydrous or monohydrate) of high purity (>98.5%), which contains an impurity spectrum characteristic of the process described above, for example less than 0.35% by weight of carbonaceous impurities.

[0097] For LiOH monohydrate, the characteristic impurities are calcium, fluorine, and sodium. Typical amounts of these in this LiOH monohydrate are as follows: Ca: 100wtppm~1.29wt% F: 0.1~1.29wt% Na: 0.1~1.29% by weight.

[0098] Furthermore, depending on the composition of the PM, significant amounts of zinc, aluminum, potassium and chlorine may be present. In these cases, the LiOH monohydrate obtained after step (e1) has characteristic amounts in the following ranges: Zn: 20wtppm~1.29wt% Al: 50wtppm~1.29wt% K: 0.1~1.29wt% Cl: 0.1~1.29% by weight.

[0099] Depending on the drying conditions, anhydrous LiOH is obtained instead of the monohydrate, in which the characteristic amounts of the above-mentioned impurities for the monohydrate are highly concentrated by a factor of 1.75 (corresponding to the molar weight of the monohydrate divided by the molar weight of the anhydrous) relative to 100% anhydrous LiOH.

[0100] All applicable steps, including steps (b), (c), (d) and (e), are preferably carried out in an inert atmosphere, such as nitrogen, argon, or in CO2-free air.

[0101] In one embodiment of the invention, Li is recovered from the solution obtained in step (c) by precipitation as Li carbonate by addition of sodium or ammonium carbonate or, preferably under pressure, by carbonic acid formed by dissolution of carbon dioxide (step e5).

[0102] In one embodiment, this Li carbonate is dissolved again by further adding CO2, preferably under pressure, to the solution to form dissolved LiHCO3 (e6). Possible impurities can be separated using prior art purification techniques, such as solvent extraction, precipitation and / or ion exchange. After this optional purification, the Li carbonate can be obtained by increasing the temperature of the solution, which directly results in the precipitation of the Li carbonate (e7). Subsequent solid-liquid separation allows the pure Li carbonate to be obtained.

[0103] In a preferred embodiment of the present invention, Li is recovered as LiOH.

[0104] The resulting solid Li salt and / or LiOH may be further purified by dissolution and recrystallization as known in the art.

[0105] The solid Ni concentrate obtained from step (c) or (d) may subsequently be subjected to step (f) in order to extract Ni and, where applicable, Co and, where applicable, other valuable metals contained in the Ni concentrate, such as Zr. For extraction, smelters or acid or ammonia leaching may be applied.

[0106] In one embodiment of the present invention, such step (f) may be pyrometallurgical by smelting the solid Ni concentrate obtained in steps (c) or (d) as itself or as a co-feed in a smelting furnace dedicated to Ni concentrate from mining production.

[0107] During such step (f), the transition metal material may be treated with a leaching agent, preferably an acid selected from sulfuric acid, hydrochloric acid, nitric acid, methanesulfonic acid, oxalic acid and citric acid, or a combination of at least two of the foregoing, such as a combination of nitric acid and hydrochloric acid. - inorganic acids, e.g. sulfuric acid, hydrochloric acid, nitric acid, organic acids, such as methanesulfonic acid, oxalic acid, citric acid, aspartic acid, malic acid, ascorbic acid or glycine, a base, such as ammonia, an amine, an aqueous solution of ammonia, ammonium carbonate, or a mixture of ammonia and carbon dioxide, or - Chelating agents, such as Na4EDTA, Na2H2EDTA, H4EDTA (in the following sections, these three chelating agents are collectively referred to as simply EDTA) or dimethylglyoxime.

[0108] In one form, the leaching agent comprises an aqueous acid, such as an inorganic or organic aqueous acid. In another form, the leaching agent comprises a base, preferably ammonia or an amine. In another form, the leaching agent comprises a complexing agent, preferably a chelating agent. In another form, the leaching agent comprises an inorganic acid, an organic acid, a base or a chelating agent.

[0109] The concentration of the leaching agent may vary within a wide range, for example in the range of 0.1 to 98% by weight, preferably between 10% and 80%. A preferred example of an aqueous acid is aqueous sulfuric acid, for example with a concentration in the range of 10 to 98% by weight. Preferably, the aqueous acid has a pH value in the range of -1 to 2. The amount of acid is adjusted so that an excess of acid with respect to the transition metal is maintained. Preferably, the pH value of the solution obtained at the end of step (f) is in the range of -0.5 to 2.5. A preferred example of a base as leaching agent is aqueous ammonia, preferably with a molar ratio of NH3 to metal (Ni, Co) of 1:1 to 6:1, preferably 2:1 to 4:1, in the presence of also carbonate or sulfate ions. Suitable chelating agents such as EDTA or dimethylglyoxime are often applied in a molar ratio of 1:1 to 3:1.

[0110] The leaching may be carried out in the presence of an oxidizing agent. A preferred oxidizing agent is oxygen, either as a pure gas or in a mixture with an inert gas, such as nitrogen, or as air. Other oxidizing agents are oxidizing acids, such as nitric acid, or peroxides, such as hydrogen peroxide.

[0111] In one embodiment of the present invention, such step (f) may be carried out by dissolving the solid Ni concentrate obtained in step (c) or (d) in an acid selected from sulfuric acid, hydrochloric acid, nitric acid, methanesulfonic acid, oxalic acid and citric acid.

[0112] In one embodiment of the present invention, such step (f) may be carried out by treating the solid Ni concentrate obtained in step (c) or (d) with an aqueous solution of ammonium carbonate or ammonium bicarbonate, which may contain additional ammonia.

[0113] In one embodiment of the present invention, the Ni concentrate obtained from step (c) or (d) is treated in step (f) with an acid selected from sulfuric acid, hydrochloric acid, nitric acid, methanesulfonic acid, oxalic acid and citric acid, or a combination of at least two of the above, for example a combination of nitric acid and hydrochloric acid. In the case of aqueous acids, the concentration of the acid may vary within a wide range, for example in the range between 0.1 and 99% by weight, preferably between 10% and 96%. The amount of acid is adjusted so that an excess of acid is maintained. Preferably, the pH value of the solution obtained at the end of step (f) is in the range of -0.5 to 2.

[0114] A preferred example of an aqueous acid is an aqueous sulfuric acid solution, for example having a concentration in the range of 10 to 98% by weight.

[0115] The treatment according to step (f) may be carried out at a temperature in the range of from 20 to 200° C., in particular from 20 to 130° C. If a temperature above 100° C. is desired, step (f) is carried out at a pressure above 1 bar. Otherwise, normal pressure is preferred.

[0116] In one embodiment of the present invention, step (f) is carried out in a container protected against strong acids, such as molybdenum and copper-rich steel alloys, nickel-based alloys, duplex stainless steel, or glass-lined or enamel- or titanium-coated steel. Further examples are polymer linings and containers made of acid-resistant polymers, such as polyethylene, e.g., HDPE and UHMPE, fluorinated polyethylene, perfluoroalkoxyalkanes ("PFA"), polytetrafluoroethylene ("PTFE"), PVDF, and FEP. FEP stands for fluorinated ethylene propylene polymer, i.e., a copolymer of tetrafluoroethylene and hexafluoropropylene.

[0117] The slurry resulting from step (f) may be stirred or agitated or subjected to a grinding process, for example in a ball mill or stirred ball mill, which often provides better access for the water or acid to the particulate transition metal material.

[0118] In one embodiment of the present invention, step (f) has a duration in the range of 10 minutes to 10 hours, preferably 1 to 3 hours. For example, the reaction mixture in step (f) is stirred or pumped at a power of at least 0.1 W / l to achieve good mixing and to avoid settling of insoluble components. Shearing can be further improved by utilizing baffles. All these shearing devices must be applied with sufficient corrosion resistance and may be manufactured from similar materials and coatings as those described for the vessel itself.

[0119] Step (f) may be carried out under an atmosphere of air or air diluted with N. However, it is preferred to carry out step (f) under an inert atmosphere, such as nitrogen or a noble gas, such as Ar.

[0120] Treatment according to step (f) dissolves metal compounds, including impurities other than carbon and organic polymers, remaining after leaching of LiOH in step (b). In most embodiments, a slurry is obtained after performing step (f). Residual lithium and transition metals, such as but not limited to nickel, cobalt, copper, and, where applicable, manganese, are often in dissolved form, e.g., in the form of salts, in the leachate.

[0121] In embodiments where a so-called oxidizing acid is used in step (f), it is preferred to add a reducing agent to remove unused oxidants. Examples of oxidizing acids are nitric acid and a combination of nitric acid and hydrochloric acid. In the context of the present invention, hydrochloric acid, sulfuric acid and methanesulfonic acid are preferred examples of non-oxidizing acids.

[0122] In one embodiment, step (f) is carried out under an inert gas, such as nitrogen or argon.

[0123] Depending on the concentration and amount of aqueous acid used in step (f), the liquid phase obtained in step (f) may have a transition metal concentration in the range of 1 up to 25% by weight, preferably 6-15% by weight. The transition metal concentration depends on the solubility of the salts corresponding to the acid employed. Preferably, to ensure a high metal concentration in solution, step (f) is carried out such that the transition metal concentrations of the main metals, e.g. Ni and possibly Co and Mn, are just below the solubility limit of the least soluble salt.

[0124] An optional step that may be performed after step (f) is the removal of non-dissolved solids, such as carbonaceous materials, and polymers originating from the battery housing. This may be performed by filtration, centrifugation, or settling and decantation, with or without the addition of flocculants. The resulting solid residue may be washed with water and may be further processed, for example by the solid-solid separation methods described above, to separate the carbonaceous and polymeric components.

[0125] In one embodiment of the present invention, step (f) and the removal of undissolved solids is carried out continuously in a continuous operation mode.

[0126] By dissolving the Ni concentrate in step (f) in the subsequent step (f1), the pH value of the above slurry or solution can be adjusted to 2.5-8, preferably 5.5-7.5, even more preferably 6-7. The pH value can be determined by conventional means, such as potentiometric titration, which refers to the pH value of the continuous liquid phase at 20° C. The adjustment of the pH value is done by dilution with water or by addition of a base, or by a combination of these. Examples of suitable bases are ammonia and alkali metal hydroxides, such as LiOH, NaOH or KOH in solid form, for example as pellets, or preferably as an aqueous solution. Combinations of at least two of the foregoing are also possible, such as ammonia and aqueous caustic soda.

[0127] Preferably, optional step (f2) comprises removing the precipitate of carbonates, oxides, phosphates, hydroxides or oxyhydroxides of Al, Cu, Fe, Zr, Zn, or a combination of at least two of the above, formed in optional step (f1). The precipitate may be formed during the adjustment of the pH value. The phosphate may be stoichiometric or basic phosphate. Without wishing to be bound by any theory, the phosphate may occur in the case of phosphate formation through hydrolysis of hexafluorophosphoric acid or its decomposition products formed during the pretreatment of the particulate material provided in this step (a). The precipitate may be removed by filtration, or by centrifugation, or by sedimentation. Preferred filters are belt filters, filter presses, suction filters and cross-flow filters. Filter aids and / or flocculants may be added to improve solid-liquid separation.

[0128] In a preferred embodiment of the present invention, step (f2) optionally comprises step (f3), which comprises treating the solution obtained after step (f1) or step (f2) with metallic nickel, metallic cobalt or metallic manganese, or any combination of at least two of the foregoing.

[0129] In optional step (f3), the solution obtained after step (f2) is contacted with metallic nickel, cobalt or manganese, or a combination of at least two of the foregoing, for example in a column. In such an embodiment, it is advantageous to provide a column packed with metallic nickel, cobalt or manganese, or a combination of at least two of the foregoing, in agglomerates or granules, for example as a fixed bed, and to allow the solution stream to flow through such column.

[0130] In one embodiment of the present invention, step (f3) is carried out at normal pressure.

[0131] In one embodiment of the invention, step (f3) has a duration ranging from 30 minutes to 5 hours, the duration corresponding to the average residence time if step (f3) is carried out in a column.

[0132] In one embodiment of the present invention, step (f3) is carried out at a pH value ranging from 1 to 6, preferably at a pH of from 2 to 5. The lower the pH value in step (f3), the more metals selected from Ni, Co and Mn dissolve under hydrogen formation.

[0133] Step (f3) is particularly useful for removing traces of copper. By carrying out step (f3), no new impurities are introduced into the solution of transition metals that would require additional purification steps. Even if the metallic nickel, cobalt or manganese contains traces of copper, these will not dissolve.

[0134] The separation of copper in step (f3) may be carried out by electrolysis, preferably using an electrochemical filter cell, using a conductive particulate material, such as graphite contained in the black agglomerates, as an electrode.

[0135] Alternatively, copper may be extracted by solvent extraction or ion exchange prior to precipitation of Al, Fe, Zr and / or Zn and recovered as high grade copper by electrowinning.

[0136] The individual metals may be recovered as pure metal salts from the mixed Ni-, Co- and / or Mn-containing solutions by procedures known in the art, such as precipitation as oxides, hydroxides, carbonates or sulfides, solvent extraction, ion exchange, electrowinning, etc. These pure metal salts may be reintroduced into the synthesis of the active cathode material, for example, by steps (g1) and (g) below.

[0137] Optional step (g) is typically carried out following step (f) and optional steps (f1), (f2), (f3) and comprises precipitating the transition metals as mixed hydroxides or mixed carbonates, preferably as mixed hydroxides.

[0138] In a preferred embodiment of the present invention, step (g) is carried out by adding ammonia or an organic amine, such as dimethylamine or diethylamine, preferably ammonia, and at least one inorganic base, such as lithium hydroxide, sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate, potassium carbonate or potassium bicarbonate, or a combination of at least two of the foregoing. It is preferred to add ammonia and sodium hydroxide.

[0139] In one embodiment of the present invention, step (g) is carried out at a temperature in the range of 10-85°C, preferably 20-50°C. In one embodiment of the present invention, the concentration of the organic amine (or ammonia) is in the range of 0.05-1 mol / l, preferably 0.1-0.7 mol / l. The term "ammonia concentration" in this context includes the concentrations of ammonia and ammonium. The Ni in the mother liquor 2+ and Co 2+ Particularly preferred is an amount of ammonia that results in a solubility of each of 1000 ppm or less, more preferably 500 ppm or less.

[0140] In one embodiment of the present invention, mixing is effected during step (g) of the method of the present invention, for example by a stirrer, rotor-stator mixer or ball mill. It is preferred to introduce a stirrer power of at least 1 W / l, preferably at least 3 W / l, more preferably at least 5 W / l, into the reaction mixture. In one embodiment of the present invention, a stirrer power of up to 25 W / l can be introduced into the reaction mixture.

[0141] Optional step (g) of the method of the present invention may be carried out in the presence or absence of one or more reducing agents. Examples of suitable reducing agents are hydrazine, primary alcohols, such as but not limited to methanol or ethanol, as well as ascorbic acid, glucose and alkali metal sulfites. It is preferred not to use any reducing agent in step (g). The use of a reducing agent or an inert atmosphere, or a combination of both, is preferred when a large amount of manganese, for example at least 3 mol % with respect to the transition metal portion of the respective cathode active material, is present in the transition metal oxide material.

[0142] Step (g) of the method of the invention may be carried out under an atmosphere of an inert gas such as, for example, nitrogen or argon or carbon dioxide.

[0143] In one embodiment of the present invention, step (g) is carried out at a pH value in the range of 9 to 13.5, preferably 11 to 12.5, for hydroxides and at a pH value in the range of 7.5 to 8.5, for carbonates. The pH values ​​refer to the pH values ​​in the mother liquor, determined at 23° C.

[0144] Step (g) may be carried out in a batch reactor or (preferably) continuously, for example in a continuous stirred tank reactor, or in a cascade of two or more, for example two or three, continuous stirred tank reactors.

[0145] Step (g) of the method of the present invention can be carried out under air, under an inert gas atmosphere, such as a noble gas or nitrogen atmosphere, or under a reducing atmosphere. An example of a reducing gas is, for example, SO2. It is preferable to operate under an inert gas atmosphere, especially nitrogen gas.

[0146] For purposes of further purification, the solid recovered in step (g) may be separated and dissolved in an acid, such as hydrochloric acid, or more preferably, sulfuric acid.

[0147] By carrying out the method of the present invention, the transition metals nickel and, if applicable, cobalt and / or manganese can be recovered from a positive electrode material containing nickel and cobalt, and, if applicable, manganese, in a form that can be very easily converted into a positive electrode active material. In particular, the method of the present invention allows the recovery of transition metals, such as nickel and, if applicable, cobalt and / or manganese, containing impurities, such as copper, iron and zinc, only in tolerably trace amounts, for example less than 10 ppm copper, preferably even less, for example 1 to 5 ppm.

[0148] In one embodiment of the present invention, in an additional step (g1) before step (g), nickel, cobalt and / or manganese salts are added to the recycled metal salt solution from step (f) or (f1), (f2) or (f3) to adjust the ratio of metals to the desired composition of the mixed metal hydroxide precipitate, which can be used as a precursor material for the production of the cathode active material. During such precipitation, additional metal salts may be added, preferably as an aqueous solution of the anion of the acid used in step (f), an example of such a metal is aluminum, which can be added as aluminum sulfate. The mixed metal hydroxide precipitate can be separated from the liquid by solid-liquid separation and dried to obtain a dry mixed metal hydroxide precipitate having a water content of 10% by weight or less. This allows the cathode active material precursor to be directly obtained in a continuous precipitation step (g). The mixed metal hydroxide precipitate obtained in step (g) can be further processed as a dry powder with a lithium salt, preferably lithium carbonate, most preferably lithium hydroxide. Preferably, the lithium salt obtained from step (e) of the process of the present invention may be dry mixed with a dry mixed metal hydroxide precipitate and subjected to a calcination process comprising a temperature range of 400-900° C., preferably 450-800° C., to obtain a mixed lithium-containing metal oxide containing nickel and / or cobalt.

[0149] In one embodiment of the present invention, the solid Ni concentrate obtained in step (d) is treated with ammonium (bi)carbonate in aqueous solution at a concentration of 0.2-30% by weight, preferably 1-20% by weight. The slurry may be heated to a temperature of 30-150° C. Above the boiling point of the mixture, the heating is carried out under pressure. Below the boiling point, the application of pressure is advantageous in order to maintain sufficient ammonia and carbon dioxide in the system.

[0150] The treatment with ammonium (bi)carbonate may be carried out under an inert atmosphere or in the presence of oxygen, e.g. under air. The leachate or solution may also contain additional ammonia and / or hydrogen peroxide.

[0151] The ammonium (bi)carbonate treatment dissolves Ni, and where applicable Co and Cu, as ammonium complexes. The concentration of metal ammonium complexes in the leach liquid may be in the range of 0.2-30 wt% by metal, preferably 1-15 wt% by metal. The solution obtained by this treatment is subjected to solid-liquid separation, resulting in a solution containing mainly ammonium complexes of Ni, and where applicable Co and Cu, and a separated solid residue containing mainly other transition metals, i.e. Mn and Fe, where applicable.

[0152] The resulting solution can be heated and the ammonia removed by purging with carbon dioxide. This results in first the Ni carbonate and, in longer treatments, advantageously at higher temperatures, also the Co carbonate as precipitates. This allows both metals to be separated. In one embodiment of the invention, the Ni and Co carbonates are not separated from each other. The precipitated mixed Ni / Co carbonate is separated from the mother liquor and dissolved in sulfuric acid or another acid to obtain a solution of the corresponding Ni salt and, if applicable, Co salt. This solution may also contain small amounts of Cu salts, which can be removed by treatment with the metals Ni, Co or Mn as described above. Other impurities such as Fe or Al, which may be present in low concentrations, can be removed by hydroxide or carbonate precipitation at pH values ​​of 2.5 to 8, also as described above.

[0153] Ni hydroxide and Co hydroxide can be co-precipitated from a solution of purified Ni salts and, where applicable, Co salts.

[0154] In one embodiment of the present invention, the solution is further processed to extract the Ni and Co salts separately, for example, by solution extraction. The pure metals can be recovered from the separated Ni and Co salts via electrochemical methods known in the art.

[0155] In one embodiment, the precipitation of the transition metals after steps (f1), (f2) and (f3) is carried out with hydrogen at elevated pressure. For this, the pH value of the solution is kept basic by the addition of ammonia and / or ammonium carbonate. This allows Ni, Co and Cu to be precipitated as metals. Certain catalysts known in the art may be added to improve this reaction. EXAMPLES

[0156] Description of method Particle size distribution measurements, including determination of D50, are performed according to ISO 13320 EN:2009-10.

[0157] Elemental analysis of lithium, calcium and manganese (performed to determine, inter alia, the Li, Ca, Mn content of the particulate material provided in step (a)); The reagents are Deionized water, hydrochloric acid (36%), K2CO3-Na2CO3 mixture (dry), Na2B4O7 (dry), hydrochloric acid 50% by volume (1:1 mixture of deionized water and hydrochloric acid (36%)). All reagents are PA grade.

[0158] Sample preparation 0.2-0.25 g of particulate material for this step (a) (typically obtained from waste lithium-ion batteries after carrying out the preliminary reduction step (i)) is weighed into a Pt crucible and K2CO3-Na2CO3 / Na2B4O7 melt digestion is applied. The sample is burned in an unshielded flame and subsequently completely ashed at 600 °C in a muffle furnace. The remaining ash is mixed with K2CO3-Na2CO3 / Na2B4O7 (0.8 g / 0.2 g) and melted until a transparent melt is obtained. The cooled melt cake is dissolved in 30 mL of water and 12 mL of 50% by volume hydrochloric acid is added. The solution is filled up to the specified volume of 100 mL. This work up is repeated three times independently and in addition a blank sample is prepared for reference purposes.

[0159] measurement The Li, Ca and Mn in the resulting solution are determined by inductively coupled plasma optical emission spectroscopy (ICP-OES). Instrument: ICP-OES Agilent 5100 SVDV; Wavelengths: Li 670.783 nm; Ca 396.847 nm; Mn 257.610 nm; Internal standard: Sc 361.383 nm; Dilution factors: Li 100, Ca 10, Mn 100; Calibration: external.

[0160] Elemental analysis of fluorine and fluorides is carried out according to the following standardized methods: DIN EN 14582:2016-12 for sample preparation for determination of total fluorine content (waste samples); detection method is ion-selective electrode measurement; DIN 38405-D4-2:1985-07 (water samples; digestion of inorganic solids followed by acid-supported distillation and fluoride determination using an ion-selective electrode).

[0161] Other metal impurities and phosphorus are similarly determined by elemental analysis using ICP-OES (Inductively Coupled Plasma Optical Emission Spectroscopy) or ICP-MS (Inductively Coupled Plasma Mass Spectroscopy). Total carbon is determined by a thermal conductivity detector after combustion.

[0162] The phase composition of the solid (including the identity of manganese(II) oxide, and Ni and Co (typically metallic) in oxidation states lower than +2 in the particulate material provided in step (a)) is determined by powder x-ray diffraction (PXRD), which is carried out as follows.

[0163] The sample is ground to a fine powder and packed into the sample holder.

[0164] It utilizes two devices, each with its own separate radiation source.

[0165] (1) Measurements applying Cu radiation: The equipment used is a Bruker D8 Advance Series 2 with an autosampling unit. Primary side: Cu anode, beam divergence angle aperture 0.1° with ASS; Secondary side: divergent beam aperture 8mm, Ni 0.5mm, Solar 4°, Lynx-Eye (3° aperture).

[0166] (2) Measurements applying Mo radiation: The equipment used is a Bruker D8 Discover A25 with an autosampling unit. Primary: Mo anode with Johansson monochromator (Mo-K-Alpha 1), axial solar 2.5°; Secondary: ASS, solar 2.5°, Lynx-Eye XE detector (3.77° aperture).

[0167] References are used to identify matches with the obtained reflection pattern. All relevant phases are well known in the literature, and the following references are consulted and used to calculate the theoretical diffraction pattern (see position and intensity of reflections in Table 1 below): a) Co x Ni 1-x : space group Fm-3m; x=0.5: Taylor et al., J. Inst. Met. (1950) 77, 585-594. x=0: Buschow et al.; J. Magn. Magn. Mater. 1983, 38, 1-22. b) Co; space group P63 / mmc; Buschow et al.; J. Magn. Magn. Mater. 1983, 38, 1-22. c) Li2CO3, space group C2 / c; J. Alloys Compd. (2011), 509, 7915-7921 d) LiAlO2, space group R-3m; Marezio et al., J. Chem. Phys. (1966) 44, 3143-3145. e) MnO, space group Fm-3m, Locmelis et al., Z. Anorg. Allg. Chem. 1999, 625, 1573.

[0168] [Table 1]

[0169] If characteristic reflections overlap with those of different crystalline phases (especially graphite, which constitutes the largest proportion of the sample), additional measurements are performed utilizing alternative radiation sources (e.g. Mo K alpha instead of Cu K alpha).

[0170] Abbreviations In the context of the present invention, normal pressure means 1 atm or 1013 mbar. "Normal conditions" means normal pressure and 20° C. Nl stands for normal liter, i.e. liter at normal conditions (1 atm, 20° C.). PFA stands for perfluoroalkoxy polymer.

[0171] Percentages refer to % by weight unless specifically defined otherwise. The expressions % by weight and wt% may be used interchangeably. Whenever mentioned, the terms "room temperature" and "ambient temperature" refer to a temperature between about 18° C. and 25° C. XRD refers to powder x-ray examination (radiation as indicated, typically Cu k-alpha 1 radiation at 154 pm or Mo k-alpha 1 radiation at 71 pm).

[0172] The present invention is further illustrated by the following examples.

[0173] [Example 1] Synthetic extract sample A quantity of 200g of simulated used battery scrap containing: 78.8 g of spent cathode active material containing nickel, cobalt, and manganese in approximately equal molar amounts and having the approximate formula Li(NiCoMn)O; 62.2 g of organic carbon in the form of graphite and soot, 47.0 g of organic electrolyte mixture (containing LiPF6), 7.4 g of polyvinylidene fluoride as binder, 2.4g aluminum powder, 0.2g iron powder, 2.0g copper metal The mixture was placed in a 500 mL quartz round-bottom flask and attached to a rotary evaporator so that the flask was immersed in the oven. The rotating flask was heated to 800°C within 4.5 h, placed under a flow of argon (20 l / h) for 2 h, held at this temperature for 1 h under a flow of dry air (20 l / h) and then cooled to ambient temperature. A quantity of 173.3 g of heat-treated material was obtained with a phase composition of Ni / Co alloy, iron manganese oxide, Li2CO3, LiF and graphite.

[0174] [Example 1a] Preparation of reduced mass from waste lithium-ion batteries A quantity of about 1 ton of mechanically processed battery scrap containing spent positive active material, containing nickel, cobalt and manganese, organic carbon in the form of graphite and soot, as well as residual electrolyte and further impurities including fluorine compounds, phosphorus and calcium among others, is treated to obtain reduced mass by the method described in Jia Li et al., Journal of Hazardous Materials 302 (2016) 97-104. The atmosphere in the roasting system is air, where oxygen reacts with the carbon in the battery scrap to form carbon monoxide, and the treatment temperature is 800°C.

[0175] After reaction and cooling to ambient temperature, the heat-treated material is recovered from the furnace and mechanically processed to obtain particulate material that is analyzed by X-ray powder diffraction (Figs. 1, 2: Mo Ka radiation; Figs. 3, 4: Cu Ka radiation), elemental analysis (Table 2) as well as particle size distribution (Table 3).

[0176] The lithium content is 3.6% by weight and serves as a reference for all further leaching examples (see below). The fluorine is mainly expressed as inorganic fluoride (88%). The particle size is well below 1 mm, with a D50 determined to be 17.36 μm.

[0177] Comparing the obtained XRD pattern with the calculated reference patterns of Ni (CoxNi1-x, which is identical to the pattern for x=0-0.6), Co, Li2CO3 and LiAlO2 (see reference patterns in Table 1), it can be concluded that Ni is present exclusively as metallic phase, either as pure Ni or as an alloy in combination with Co. For clarity, this result is confirmed by applying two different radiation sources. The presence of metallic nickel is supported by the qualitative observation that the whole sample, when contacted with a permanent magnetic material, shows a typical ferromagnetic behavior. As lithium salts, Li2CO3 and LiAlO2 are unambiguously identified by their characteristic diffraction patterns.

[0178] The composition of the obtained black powder (PM) is shown in Table 2.

[0179] [Table 2]

[0180] [Table 3]

[0181] [Example 2] Leaching with Ca(OH)2 A quantity of 5 g of the above-mentioned reduced battery scrap material (obtained as shown in Example 1a) is loaded into a PFA flask and mixed with 5, 1.5, 1.0 and 0.5 g of solid Ca(OH)2, respectively. 200 g of water is added under stirring and the whole mixture is refluxed for 4 hours.

[0182] After 4 hours, the solids are filtered off and a filtrate sample is taken and analyzed for Li, F, Carbonate, OH and Ca. The results are summarized in Table 4 below.

[0183] [Table 4]

[0184] [Example 2a] Leaching with Ca(OH)2, adding solid to liquid Example 2 is repeated, except that 5 g of the black powder obtained as shown in Example 1a and the indicated amount of solid Ca(OH)2 are added simultaneously to 200 g of water under stirring. The results are similar to those reported in Table 4.

[0185] [Example 3] More solids The particulate material (PM) described in Example 1a in amounts of 10, 20 and 30 g is respectively loaded into a PFA flask and mixed with solid Ca(OH)2 in a fixed weight ratio of PM:Ca(OH)2=3.3:1. Each sample is further treated by adding 200 g water following Example 2, except that it is refluxed for 6 hours. The results are shown in Table 5.

[0186] Based on these results, we conclude that the efficiency of the present leaching process is not affected by the PM solids content.

[0187] [Table 5]

[0188] [Example 4] Parameter Variation Following the procedure of Example 2a, solid Ca(OH)2 and particulate material (PM) as described in Example 1a are added to 836.8 g of preheated water in a baffled glass reactor with stirring (three-stage cross-beam stirrer, 60 mm diameter). After continued stirring at constant temperature for the period (t) indicated in Table 6, the solids are filtered off and a filtrate sample is analyzed. The amount of Ca(OH)2 and PM, temperature, stirring parameters, and analytical results (%=g found in 100 g filtrate) are also summarized in Table 6.

[0189] [Table 6]

[0190] [Example 5] Solid LiOH from leached lithium filtrate The filtrate obtained from the process according to Example 2 is further treated by step (e1) above to obtain solid LiOH as monohydrate: 1 L of the filtrate containing 0.21 wt. % lithium is concentrated by evaporation (40° C., 42 mbar) and finally dried at 40° C. and constant flow of nitrogen for 24 hours. FIG. 5 shows the obtained LiOH monohydrate containing traces of the impurity Li2CO3, due to contact with air during almost all process steps. Elemental analysis reveals carbonaceous impurities followed by F, Na, Ca, K as main impurities (>200 ppm) and Al and Zn as trace impurities (<200 ppm). The present invention includes the following aspects. [Section 1] 1. A method for recovering lithium from materials including waste lithium ion batteries or parts thereof, comprising: (a) providing a particulate material containing a transition metal compound and / or transition metal, the transition metal being selected from the group consisting of Mn, Ni and Co, and further wherein at least a portion of said Ni and / or Co, if present, is in an oxidation state lower than +2, and at least a portion of said Mn, if present, is a manganese (II) oxide, the particulate material further containing a lithium salt and a fluoride salt, the particulate material optionally containing calcium, with the proviso that the elemental ratio of calcium to fluorine is less than or equal to 1.7 or zero; (b) treating the material provided in step (a) with a polar solvent and an alkaline earth hydroxide; and (c) separating the solid from the liquid, optionally followed by washing the solid residue with a polar solvent, e.g. water. A method comprising: [Section 2] Item 2. The method according to item 1, wherein the particulate material provided in step (a) is obtained from waste lithium ion batteries, in particular cell materials thereof, and is provided in the form of a dry powder, a wet powder or a suspension of particles in a liquid. [Section 3] Item 3. The method according to item 1 or 2, wherein the particulate material provided in step (a) comprises particles having an average particle diameter D50 in the range of 1 μm to 2 mm, as measured according to ISO 13320 EN:2009-10. [Section 4] The method according to any one of paragraphs 1 to 3, wherein the transition metal compound and / or transition metals Ni and / or Co in an oxidation state lower than +2 contained in the particulate material prepared in step (a) comprise Ni and / or Co in the metallic state, and the transition metal compound and / or transition metal contained in the particulate material prepared in step (a) are preferably present in an amount detectable by powder x-ray diffraction (Cu-k-alpha-1 radiation). [Section 5] 5. The method according to any one of claims 1 to 4, wherein the lithium salts and fluoride salts contained in the particulate material prepared in step (a) include one or more salts of LiOH, LiF, Li2O, Li2CO3, LiHCO3, lithium aluminate, lithium phosphate, mixed oxides of Li and one or more of Ni, Co, Mn, Fe, Al, and Cu, and / or fluorides of Ni, Co, Mn, Fe, Al, and Cu. [Section 6] Step (b) i) adding simultaneously to a polar solvent, which is a protic solvent, preferably an aqueous liquid, an alkaline earth hydroxide and / or an alkali oxide, as a solid, or a mixture comprising an alkaline earth hydroxide, as a suspension or solution in a protic solvent, e.g. an aqueous liquid, and the particulate material provided in step (a) By or ii) adding the particulate material provided in step (a) to a polar solvent, preferably a protic solvent, preferably an aqueous liquid, e.g. water, to obtain a suspension, followed by addition of an alkaline earth hydroxide and / or an alkali oxide as a solid, or a mixture comprising an alkaline earth hydroxide as a suspension or solution in a protic solvent, typically an aqueous liquid. By or iii) adding an alkaline earth hydroxide and / or alkali oxide, either as a solid or as a suspension of the solid in a polar solvent, to an aqueous liquid, e.g. water, to obtain a mixture comprising the alkaline earth hydroxide, typically as a suspension or solution in the aqueous liquid, and subsequently combining said mixture with the particulate material provided in step (a); By or iv) adding alkaline earth hydroxide and / or alkali oxide, as a solid, to the particulate material provided in step (a) to obtain a mixture of solids, followed by addition of a polar solvent, which is a protic solvent, preferably an aqueous liquid, e.g. water. By or v) adding the particulate material provided in step (a) to a polar solvent, preferably an aqueous liquid, such as water, to obtain a suspension, followed by filtering to obtain a filtrate, and subsequently adding to the filtrate an alkaline earth hydroxide and / or an alkali oxide as a solid, or a mixture comprising an alkaline earth hydroxide, typically as a suspension or solution in a polar solvent, preferably an aqueous liquid. The method according to any one of items 1 to 5, wherein the method is carried out by [Section 7] 7. The method according to any one of the preceding claims, wherein the alkaline earth hydroxide added in step (b) is calcium hydroxide added as such or calcium hydroxide is formed in situ upon contact of calcium oxide with a polar solvent which is a protic solvent, for example an aqueous liquid or water. [Section 8] 8. The method according to any one of items 1 to 7, wherein the particulate material provided in step (a) comprises material obtained from discarded lithium ion batteries after a preliminary step (i) of heating to a temperature in the range of 80 to 900 ° C, in particular 200 to 800 ° C, under inert or reducing conditions, the preliminary step (i) typically being carried out after discharging, dismantling and / or crushing the lithium ion batteries. [Section 9] 9. The method of claim 8, wherein the heating step (i) is carried out under reducing conditions comprising the presence of carbon and / or a reducing gas selected from hydrogen and carbon monoxide. [Section 10] Item 10. The method according to item 8 or 9, wherein in the preliminary step (i), the heating temperature is within a range of 350 to 500° C., particularly 350 to 450° C., and preferably, step (i) is carried out in the presence of 35 vol. % or more of hydrogen. [Section 11] 11. The method according to any one of paragraphs 1 to 10, wherein the particulate material provided in step (a) is obtained from a lithium ion battery after mechanical removal of the casing, wiring or circuitry and discharging, and the material is not exposed to a temperature of 400° C. or higher under oxidizing conditions prior to subjecting the material to step (a). [Section 12] 12. The method according to any one of the preceding claims, comprising an additional step (d) of subjecting the solid obtained in step (c) to solid-solid separation. [Section 13] 13. The process according to any one of paragraphs 1 to 12, comprising an additional step (f): recovery of the transition metals nickel and / or cobalt by pyrometallurgical or hydrometallurgical treatment of the solid residue obtained after carrying out step (c) or (d). [Section 14] 12. The process according to any one of the preceding claims, comprising the additional step of recovering lithium as lithium hydroxide from the liquid obtained in step (c) by crystallization or as lithium carbonate after adding carbon dioxide to the liquid obtained in step (c) and isolating the lithium carbonate formed. [Section 15] 12. A solid, particularly in the form of a particulate material, obtainable in step (c) of the process according to any one of claims 1 to 11, containing calcium, lithium and at least one of Ni, Co and Mn, where at least a portion of the Ni and / or Co, if present, is in the metallic state and where at least a portion of the Mn, if present, is manganese(II) oxide, A solid, characterized in that the weight ratio of (Ni+Co+Mn):Li in said solid is in the range of 30:100000, said solid containing 2-35% calcium by weight of the dry solid. [Section 16] 15. A lithium hydroxide product obtained by crystallization from the liquid separated in step (c) of the process according to any one of claims 1 to 11 or 14, Lithium hydroxide monohydrate containing 100 ppm to 1.29% calcium, 0.1 to 1.29% fluorine, and 0.1 to 1.29% sodium; or Anhydrous lithium hydroxide containing 175 ppm to 2.26% calcium, 0.175 to 2.26% fluorine, and 0.175 to 2.26% sodium All amounts are by weight of dry solids, lithium hydroxide product. [Section 17] 17. The lithium hydroxide product according to claim 16, obtained by crystallization from the liquid separated in step (c) of the process according to any one of claims 1 to 11 or 14, Lithium hydroxide monohydrate containing 100 ppm to 1.29% calcium, 0.1 to 1.29% fluorine, 0.1 to 1.29% sodium, 20 ppm to 1.29% zinc, 50 ppm to 1.29% aluminum, 0.1 to 1.29% potassium, and 0.1 to 1.29% chlorine; or Anhydrous lithium hydroxide containing 175 ppm to 2.26% calcium, 0.175 to 2.26% fluorine, 0.175 to 2.26% sodium, 35 ppm to 2.26% zinc, 87 ppm to 2.26% aluminum, 0.175 to 2.26% potassium, and 0.175 to 2.26% chlorine. All amounts are by weight of dry solids, lithium hydroxide product.

Claims

1. 1. A method for recovering lithium from materials including waste lithium ion batteries or parts thereof, comprising: (a) providing a particulate material containing a transition metal compound and / or a transition metal, the transition metal being selected from the group consisting of Mn, Ni and Co, and further wherein at least one of the Ni and Co, if present, is in an oxidation state lower than +2, and wherein at least a portion of the Mn, if present, is a manganese (II) oxide, the particulate material further comprising a lithium salt and a fluoride salt, the particulate material either containing or not containing calcium, with the proviso that the elemental ratio of calcium to fluorine is less than or equal to 1.7 or is zero; (b) treating the material provided in step (a) with a polar solvent and an alkaline earth hydroxide; and (c) separating the solid from the liquid. Including, 1. A method according to claim 1, wherein the particulate material provided in step (a) is obtained from a lithium ion battery after mechanical removal of any casing, wiring or circuitry and discharging, and said material has not been exposed to temperatures of 400°C or greater under oxidizing conditions prior to subjecting it to step (a).

2. 2. The method of claim 1, wherein the particulate material provided in step (a) is obtained from discarded lithium ion batteries and is provided in the form of a dry powder, a wet powder or a suspension of particles in a liquid.

3. 3. The method of claim 1 or 2, wherein the particulate material provided in step (a) comprises particles having a mean particle diameter D50 in the range of 1 μm to 2 mm, as detected according to ISO 13320 EN:2009-10.

4. 4. A method according to any one of claims 1 to 3, wherein the transition metal compounds and / or transition metals Ni and / or Co in an oxidation state lower than +2 contained in the particulate material prepared in step (a) comprise Ni and / or Co in the metallic state, and the transition metal compounds and / or transition metals contained in the particulate material prepared in step (a) are present in an amount detectable by powder x-ray diffraction (Cu-k-alpha-1 radiation).

5. 5. A method according to any one of claims 1 to 4, wherein the lithium salts and fluoride salts contained in the particulate material provided in step (a) comprise one or more salts of LiOH, LiF, Li2O, Li2CO3, LiHCO3, lithium aluminate, lithium phosphate, mixed oxides of Li and one or more of Ni, Co, Mn, Fe, Al, Cu, and / or fluorides of Ni, Co, Mn, Fe, Al, Cu.

6. Step (b) i) adding simultaneously to a polar solvent, which is a protic solvent, a mixture comprising an alkaline earth hydroxide and / or an alkali oxide as a solid, or an alkaline earth hydroxide as a suspension or solution in a protic solvent, and the particulate material provided in step (a); By or ii) adding the particulate material provided in step (a) to a polar solvent, which is a protic solvent, to obtain a suspension, followed by adding an alkaline earth hydroxide and / or an alkali oxide as a solid, or a mixture comprising an alkaline earth hydroxide as a suspension or solution in the protic solvent. By or iii) adding an alkaline earth hydroxide and / or an alkali oxide, either as a solid or as a suspension of the solid in a polar solvent, to the aqueous liquid to obtain a mixture comprising alkaline earth hydroxide, and subsequently combining said mixture with the particulate material provided in step (a); By or iv) adding an alkaline earth hydroxide and / or an alkali oxide, as a solid, to the particulate material provided in step (a) to obtain a mixture of solids, followed by adding a polar solvent, which is a protic solvent. By or v) adding the particulate material provided in step (a) to a polar solvent, which is a protic solvent, to obtain a suspension, followed by filtering to obtain a filtrate, and then adding to the filtrate a mixture comprising an alkaline earth hydroxide and / or an alkali oxide as a solid, or an alkaline earth hydroxide as a suspension or solution in the polar solvent. The method according to any one of claims 1 to 5, wherein the method is carried out by

7. 7. A method according to any one of claims 1 to 6, wherein the alkaline earth hydroxide added in step (b) is calcium hydroxide which is added as such or calcium hydroxide is formed in situ upon contact of calcium oxide with a polar solvent which is a protic solvent.

8. 8. The method according to any one of claims 1 to 7, wherein the particulate material provided in step (a) comprises material obtained from discarded lithium ion batteries after a preliminary step (i) of heating to a temperature in the range of 80-900°C under inert or reducing conditions, the preliminary step (i) being carried out after discharging, dismantling and / or crushing the lithium ion batteries.

9. 9. The method of claim 8, wherein the heating step (i) is carried out under reducing conditions comprising the presence of carbon and / or a reducing gas selected from hydrogen and carbon monoxide.

10. 10. The method according to claim 8 or 9, wherein in the preliminary step (i) the heating temperature is in the range of 350 to 500°C.

11. 11. The process according to any one of claims 1 to 10, comprising an additional step (d) of subjecting the solid obtained in step (c) to solid-solid separation.

12. 12. The process according to any one of claims 1 to 11, comprising an additional step (f): recovery of the transition metals nickel and / or cobalt by pyrometallurgical or hydrometallurgical processing of the solid residue obtained after carrying out step (c).

13. 11. The process according to any one of claims 1 to 10, comprising the additional step of recovering lithium as lithium hydroxide from the liquid obtained in step (c) by crystallization or as lithium carbonate after adding carbon dioxide to the liquid obtained in step (c) and isolating the lithium carbonate formed.

Citation Information

Patent Citations

  • Method for separating and recovering valuable material from used lithium ion battery

    JP2012229481A

  • Treatment method of lithium ion battery waste

    JP2015203131A

  • Spherical particles, production and use thereof

    WO2014180743A1

  • Method and apparatus for recycling lithium-ion batteries

    WO2017091562A1